Culturally Responsive Language and Literacy Instruction With Native American Children. Issue 2 (April 2021) - Gillispie, Matthew
Abstract : Many American Indian education leaders advocate for the need to combine evidence-based reading instruction with cultural-based educational practices. In the broader education literature, education philosophers propose analogous models such as culturally responsive teaching to meet the educational realities of diverse students. Culturally Responsive Early Literacy Instruction (CRELI) was a project funded by the U.S. Office of Special Education Programs to train graduate scholars in speech–language pathology to work with American Indian/Alaska Native communities. The grant scholars and staff of CRELI worked with two early childhood education centers for American Indian preschoolers and developed curriculum units that featured culturally relevant storybooks as thematic centerpieces and activities to facilitate early language and literacy development. This clinical tutorial summarizes this work, broader components of culturally responsive teaching, and attributes of language-focused literacy curriculum and differentiated instruction, followed by a sample curriculum unit to demonstrate application of culturally responsive teaching concepts.